Nanomaterials advancements for enhanced contaminant removal in wastewater Treatment: Nanoparticles, Nanofibers, and Metal-Organic frameworks (MOFs) - Doaa Zamel; Atta Ullah Khan; Abdul Waris; Asmaa Ebrahim; Nour E.A. Abd El-Sattar (Results in Chemistry, 2023)
Wastewater is not only a problem but also a precious source of water that has to be utilized wisely to solve the issue of the water crisis. Prior efforts have been exerted towards wastewater treatment and recycling. However, more solutions are still required to eliminate the water crisis over the entire world. As known, modernization increases water crisis problems over time. That's why scientists need to introduce new insights and materials to offer alternative approaches for wastewater treatment to be ready for usage to face the high demand for water in industry, agriculture, etc. Nanotechnology has played a magic role in the last decades in wastewater treatment by shaping materials into morphologies such as particles, rods, spheres, fibres, etc. These morphologies have higher surface areas and pore-sized structures than bulk materials, leading to their significant efficiencies and adsorption capacities. However, new ideas and insights must be incorporated for better solutions with fewer cost properties. This review explores the role of nanoparticles, nanofibers, and Metal-Organic Frameworks (MOFs) in wastewater treatment, focusing on their unique properties and applications for contaminant removal. Nanoparticles, with their high surface area-to-volume ratio and distinctive physicochemical properties, exhibit remarkable capabilities in adsorption, catalysis, and disinfection processes. Nanofibers, characterized by their high surface area and mechanical strength, are well-suited for membrane-based separation processes, offering improved removal of suspended solids and microorganisms. MOFs, three-dimensional structures with tunable porosity and surface chemistry, present a versatile platform for targeted adsorption and catalysis of pollutants.